PENERAPAN METODE BRAINSTORMING PADA PEMBELAJARAN MATERI PEMANASAN GLOBAL DI KELAS VII DI SMPN 13 PEKANBARU - Anggraini, Mega Diana; irianti, Mitri; M. Nor, M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the cognitive learning outcomes of students with the application of brainstorming on global warming material in class VII SMP 13 Pekanbaru. This type of research is a pre experiment with the research design is intact group comparison. The subject of the research was VII grade students of SMP Negeri 13 Pekanbaru in Academic Year 2018/2019. The instrument used to collect data in this study was a matter of learning achievement tests. Data were analyzed descriptively to describe student learning outcomes after using the Brainstorming learning method. The results of the analysis of the data obtained are, the average absorptive capacity of the experimental class is higher than the average absorptive capacity of the control class with an average absorbance score of the experimental class 74.31 and the average absorptive score of the control class 65.28. Learning effectiveness refers to the average absorptive score of each class, the experimental class including the effective category and the control class including the quite effective category. Thus the Brainstorming method is effectively applied to global warming material.Key Words : Brainstorming, Learning Outcomes, Global Warming